A Compendium of Multi‐Item Scales Utilized in Logistics Research (2001–10): Progress Achieved Since Publication of the 1973–2000 Compendium. Issue 2 (11th June 2013) - Keller, Scott B.; Hochard, Kimberly; Rudolph, Thomas; Boden, Meaghan
<x xml:space="preserve">Abstract</x> Forty years have passed since the first multi‐item measurement scales were employed through survey research to better understand important logistics concepts. Through the years, four leading logistics journals have published research containing a total of 1, 670 scales within 283 articles. A 42% increase in utilization has occurred during the most recent decade. The research fully discloses the conceptualization, composition, and properties of the multi‐item survey scales utilized in the study of logistics and supply chain management theory and practice. By documenting each scale published from 2001 to 2010, the authors make comparisons with results from the 1973–2000 study. Primary findings indicate an increase in the percentage of research utilizing multi‐item scales, and an increase in the application of confirmatory factor analysis (CFA) has assisted in producing more highly acceptable psychometric properties of the scales. This implies that researchers are utilizing more highly developed scales and following strict scale‐development procedures for building more robust scales to measure concepts important for advancing our knowledge of logistics and supply chain management. The top four conceptual categories for the scales have remained the same since 1973 and account for greater than half of the scales published. Eight additions to the categories since 2001 pertain greatly to controlling our supply chains for customer, brand, and overall security benefits. The compendium of scales provides a central document to reference as researchers seek to employ highly developed survey measures.